Enhancing Compressive Strength of Self-Compacting Concrete (SCC) through Rice Husk Ash and Superplasticizer Incorporation - Olii, Muhammad Ramdhan; Ali, Azhar Zukur Putra M.; Djau, Rahman Abdul; Doda, Nurhayati; Olii, Rizky Selly Nazarina (Universitas Negeri Gorontalo, 2025)
The increasing demand for sustainable construction materials has encouraged the utilization of alternative materials, such as rice husk ash (RHA), and the use of chemical admixtures like superplasticizers in self-compacting concrete (SCC). This study aims to evaluate the effects of RHA and superplasticizer incorporation on the fresh and hardened properties of SCC, focusing on flowability, segregation resistance, and compressive strength. The experimental program involved three SCC mixtures: normal concrete, and SCC with 4% and 8% RHA and superplasticizer by cement weight. Fresh concrete properties were assessed using the slump flow, V-Funnel, and L-Box tests, while compressive strength tests were conducted on cube specimens after 28 days of curing. The results indicated that the addition of 4% RHA and superplasticizer enhanced the compressive strength to 34.02 MPa and maintained flowability within the specified limits, with an average slump flow diameter of 675–697 mm, V-Funnel time of 7.35–8.72 seconds, and L-Box ratio of 0.84–0.85. However, the 8% RHA mixture exhibited a decline in compressive strength (28.51 MPa), highlighting the detrimental effects of excessive superplasticizers on particle cohesion. Furthermore, the use of RHA reduced concrete density, showcasing its potential for lightweight construction applications. These findings confirm that a 4% RHA and superplasticizer dosage optimizes SCC performance, supporting sustainable construction through resource-efficient and durable materials. The study underscores the need for precise mix designs and suggests broader applications of RHA and chemical admixtures in advancing green concrete technologies.